ТРАНСФОРМАЦІЯ МІЖБЮДЖЕТНИХ ВІДНОСИН В УМОВАХ РЕАЛІЗАЦІЇ БЮДЖЕТНОЇ РЕФОРМИ (Світ фінансів, 2017)
Проць Н. В. Трансформація міжбюджетних відносин в умовах реалізації бюджетної реформи. Досліджено сутність та причини виникнення міжбюджетного регулювання. Висвітлено актуальні питання та особливості вирівнювання дохідної спроможності місцевих бюджетів в умовах реалізації бюджетної реформи в Україні. На прикладі місцевих бюджетів Волинської області доведено, що законодавчі нововведення не забезпечать очікувану урядом фінансову автономію органів місцевого самоврядування. Запропоновано нову трансфертну модель міжбюджетних відносин впроваджувати поступово, спочатку на окремих пілотних регіонах і лише після детального вивчення відповідного досвіду поширювати на територію усієї України. Проц Н. В. Трансформация межбюджетных отношений в условиях реализации бюджетной реформы. Исследована сущность и причины возникновения межбюджетного регулирования. Проанализированы актуальные вопросы и особенности выравнивания доходной способности местных бюджетов в условиях реализации бюджетной реформы в Украине. На примере местных бюджетов Волынской области доказано, что законодательные нововведения не обеспечат ожидаемую правительством финансовую автономию органов местного самоуправления. Предложено новую трансфертную модель межбюджетных отношений внедрять постепенно, сначала на отдельных пилотных регионах и только после детального изучения соответствующего опыта распространять по территории всей Украины. Prots N. Changes in intergovernmental fiscal relations under the budget reform and its implementation. The effective implementation of the constitutional guarantees by local governments depends both on the enshrined in current legislation mechanism forming local budgets and the development of the inter-system regulation. The author determined that the system balancing the local budgets was changed under the budget reform. It is based on the baseline subsidies fixed to align revenue capacity of local budgets. Their amount depends on the index of ability to pay taxes and the extension of educational grants, subsidies for training of regular labor forces; medical subsidies whose distribution between the respective budgets is based on formulas; introduction of new interest on deductions from state taxes (the income tax, enterprise environmental tax, and personal income tax) in favor of local budgets as well as levies collected from the retail of excise goods at a rate in the range of 2% up to 5% of the cost of sold goods and imposed instead of the fee for wine growing, gardening and hop growing as the local budgets. The loss in incomes of the local budgets of Volyn region through the transfer of 25% tax on personal incomes to the state budget of 2015 will be compensated by only 90% whilst the regional budget – by 19.5 % . This phenomenon has been studied in the context of the new version of the Budget Code of Ukraine. These changes caused a signifi cant loss of financial resources of local budgets with a low taxpaying power. The author proves that legislative innovations will not provide the expected government financial autonomy of the local authorities because of the transfer of additional income sources for communities secured an enormous amount of new spending, including nearly all of them being transferred to education, medicine, culture, roads and utilities. Transfer policy in the new model budget relations in Ukraine provides only horizontal alignment of fiscal territories. Suggested a new transfer model interbudgetary relations implemented gradually, first in pilot regions and only after a detailed study of relevant experience spread across the territory of Ukraine.